Effect of tropical fruit pulps infusion during second fermentation of cannabis leaves based-kombucha on quality characteristics and its storage changes - A’yuni, Qurrata; Pirak, Tantawan (Agriculture and Natural Resources, 2024)
Importance of the work: With the rising demand for functional beverages, kombucha gained its interest due to the health benefits; however, the taste was harsh and hard to drink which was resolved with the second fermentation. Objectives: To investigate the effects of fruit infusion during second fermentation of Kombucha on quality characteristics and storage changes of cannabis leaves based-kombucha. Materials and Methods: The first fermentation was prepared with 30% cannabis leaves infusion and fermented at 25°C for 7 days to receive the cannabis leaves based-kombucha. The second fermentation was performed by infusing blended pulps of cantaloupe, mahachanok mango or tangerine (10% and 15% v/v) into the cannabis leaves based-kombucha prior to ferment at 25°C for 24 hours. The qualities of all treatments were analyzed, and the microbial changes were monitored. The criteria of the sample selection were based on the quality and lactic acid bacteria (LAB) counts. The changes during storage periods at 4 ± 2°C, 30 days were then investigated. Results: The cannabis leaves based-kombucha infused with fruit pulp had higher LAB counts (6.57–6.71 log CFU/mL), polyphenol contents (0.80–0.96 mg GAE/mL) and antioxidant properties (4.70–5.11 mg Trolox/mL) compared to the control treatment. The phytochemicals and sufficient nutrients obtained from the fruit enhanced the LAB growth which resulted in lowering acetic acid obtained from the first kombucha fermentation. Better physical and chemical quality properties were enhanced. The color quality changes were influenced by pH and total acidity alterations. The selected kombucha using 10% tangerine pulp maintained its quality properties, without pathogenic microorganisms detected after 30 days of refrigerated storage, suggesting it remained acceptable and safe for consumption. Main finding: The addition of fruits during the second fermentation of kombucha could effectively improve the kombucha quality with beneficial functions. The enhancement of flavor, overall qualities and LAB viability resulted.